Utility Serum Marker HE4 for the Differential Diagnosis Between Endometriosis and Adnexal Malignancy. Issue 1 (January 2016) - Zapardiel, Ignacio; Gorostidi, Mikel; Ravaggi, Antonella; Allende, Maria T.; Silveira, Margarida; Abehsera, Daniel; Macuks, Ronalds
Abstract : Objective: The aim of the study was to assess the utility of serum human epididymal secretory protein E4 (HE4) biomarker in the differential diagnosis of endometriosis and adnexal malignancies. Methods: Multicentric prospective observational study between January 2010 and December 2011 in 4 European centers (Italy, Portugal, Latvia, and Spain) was carried out. We collected 981 healthy patients diagnosed with adnexal patology and selected 65 patients diagnosed with endometriosis and analyzed their serum markers CA125, HE4, and Risk of Ovarian Malignancy Algorithm (ROMA) index. We also analyzed all cases of malignant histology and divided them according to CA125 levels (negative, ⩽35 U/mL; intermediate, >35–150 U/mL; and highly positive, >150 U/mL). Results: HE4 was positive only in 1.5% of cases, CA125 in 64.6%, and ROMA index in 14.1%. In the subgroup intermediate CA125 values, positive HE4 is very specific (91.2%) correctly classifying patients with benign disease, but with lower sensibility (66.1%); however, ROMA index showed a high sensibility (89.3%), with a false-positive rate of 42.8%. Conclusions: HE4 can be a very useful biomarker to exclude malignant disease in patients with endometriosis.